Increased Stroke Risk Following Herpes Zoster Infection and Protection With Zoster Vaccine. (7th July 2022) - Parameswaran, Ganapathi Iyer; Wattengel, Bethany A; Chua, Hubert C; Swiderek, Jessica; Fuchs, Tom; Carter, Michael T; Goode, Laura; Doyle, Kathleen; Mergenhagen, Kari A
Abstract: Background: Studies evaluating stroke following varicella zoster virus (VZV) infection are limited, and the utility of zoster vaccination against this phenomenon is unclear. This study aimed to determine the risk of stroke 30 days following zoster infection and to evaluate the impact of zoster vaccinations on the risk of stroke in VZV-infected patients. Methods: This retrospective case-control study was conducted from January 2010 to January 2020 utilizing nationwide patient data retrieved from the Veterans Affairs' Corporate Data Warehouse. Results: A total of 2 165 505 patients ≥18 years of age who received care at a Veterans Affairs facility were included in the study, of whom 71 911 had a history of zoster infection. Zoster patients were found to have 1.9 times increased likelihood of developing a stroke within 30 days following infection (odds ratio [OR], 1.93 [95% confidence interval CI, 1.57–2.4]; P < .0001). A decreased risk of stroke was seen in patients who received the recombinant zoster vaccine (OR, 0.57 [95% CI, .46–.72]; P < .0001) or the live zoster vaccine (OR, 0.77 [95% CI, .65–.91]; P = .002). Conclusions: Patients had a significantly higher risk of stroke within the first month following recent herpes zoster infection. Receipt of at least 1 zoster vaccination was found to mitigate this increased risk. Vaccination may therefore be viewed as a protective tool against the risk of neurologic postinfection sequelae. Abstract : Patients had significantly higher risk of stroke within the first month following herpes zoster infection. Receipt of at least 1 dose of zoster vaccination was found to mitigate this risk. Zoster vaccination mitigates risk of infection and neurologic postinfection sequelae.